Negotiating invisible lines: Cross-border emergency care in the rural north of Scandinavia. Issue 3 (27th May 2019) - Schwarzenberg, Tom
ABSTRACT: Cross-border cooperation is increasingly practised as a spatial planning strategy in health care. This observation is emphasized in numerous reports on transboundary agreements in European border regions. While the projects hint at an ongoing contestation and reconfiguration of nationally bordered health care pathways, they have rarely been subject to critical geographical inquiry. Departing from contemporary border studies debates, the article addresses this gap by providing a nuanced perspective on the socio-spatial complexity of health care practices across Europe's internal borders. The author demonstrates this empirically by focusing on a framework for emergency care assistance in the northernmost regions of Scandinavia. He uses a heuristic approach to borderscapes as assemblages, and conceptually argues that the strategic reconfiguration of emergency care provision through cross-border cooperation is not adequately captured by a narrative of dissolving topographically bordered sovereignty (i.e. the commonplace notion of overcoming national boundaries). Based on a qualitative analysis of motives, procedures and hurdles, the author concludes that the attempt to cope with demography and distance in rural northern health care formats a socio-spatial arrangement in its own right, a case-specific geography of emergency care that is characterized by a complex interplay between different sites and their multiple bordering trajectories.